Functionalized carbophenes as high-capacity versatile gas adsorbents: An ab initio study - Junkermeier, Chad E.; Larmand, Evan; Morais, Jean-Charles; Kobebel, Jedediah; Lavarez, Kat; Adra, R. Martin; Yang, Jirui; Diaz, Valeria Aparicio; Paupitz, Ricardo [UNESP]; Psofogiannakis, George (Elsevier, 2024)
This study employs density functional theory (DFT) and density functional tight-binding theory (DFTB) to determine the adsorption properties of carbon dioxide (CO2), methane (CH4), and dihydrogen (H2) in carbophenes functionalized with carboxyl (COOH), amine (NH2), nitro (NO2), and hydroxyl (OH) groups. We demonstrate that carbophenes are promising candidates as adsorbents for these gasses. Carbophenes have larger CO2 and CH4 adsorption energies than other next-generation solid-state capture materials. Yet, the low predicted desorption temperatures mean they can be beneficial as air scrubbers in confined spaces. Functionalized carbophenes have H2 adsorption energies usually observed in metal-containing materials. Further, the predicted desorption temperatures of H2 from carbophenes lie within the DOE Technical Targets for Onboard Hydrogen Storage for Light-Duty Vehicles (DOEHST) operating temperature range. The possibility of tailoring the degree of functionalization in combination with selecting sufficiently open carbophene structures that allow for multiple strong interactions without steric hindrance (crowding) effects, added to the multiplicity of possible functional groups alone or in combination, suggests that these very light materials can be ideal adsorbates for many gases. Tailoring the design to specific adsorption or separation needs would require extensive combinatorial investigations.
Keywords: 2-dimensional materials; Carbophene; Covalent organic framework; Greenhouse gas adsorption; Hydrogen adsorption; Porous materials